2020
DOI: 10.1093/zoolinnean/zlaa025
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic reassessment ofParasesarma(Crustacea: Brachyura: Decapoda: Sesarmidae) based on genetic and morphological comparisons, with the description of a new genus

Abstract: Parasesarma is a species-rich genus whose representatives are common in wetlands and mangroves of the Indo-Pacific. Morphologically, the genus is heterogeneous and has been postulated to constitute a polyphyletic taxon. In the present study, most species of Parasesarma are re-evaluated phylogenetically, using mitochondrial and nuclear molecular markers. The results show that the majority of the examined species cluster consistently with the type species Parasesarma plicatum. However, some species, among them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Previous phylogenetic analyses on species of Parasesarma [ 36 , 49 , 57 , 81 ] revealed that members of the P . bidens species complex from the Western Pacific ( P .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous phylogenetic analyses on species of Parasesarma [ 36 , 49 , 57 , 81 ] revealed that members of the P . bidens species complex from the Western Pacific ( P .…”
Section: Discussionmentioning
confidence: 99%
“…guttatum . Under a larger clade, these six species form two reciprocally monophyletic groups, a western clade versus an eastern one [ 36 , 49 , 57 , 81 ]. This pattern highlights the importance of the Indo-Pacific barrier [ 31 ] in structuring phylogeny of these marine invertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations